The influence of infection in the urinary tract of sows on arthritis, facial lesions and weight gain in suckling piglets (Research, Society and Development, 2020)
Urinary tract infection (UTI) is a common disease in sows, it influences their yield and can also affect piglets. There is a small number of studies in the literature reporting close correlation between UTI in sows and disease development or reduced performance in piglets. Therefore, the aim of the present study is to test whether UTI in pregnancy influences disease development and the growth performance of suckling piglets. Healthy sows, presenting parity 1 to 4, were divided into two groups: UTI (+) (36 sows with UTI) and UTI (-) (36 sows without UTI). After delivery, piglets were monitored for diarrhea, omphalitis, arthritis and facial lesions. Average weaning weight (AWW) was calculated to measure growth performance. There was no difference in diarrhea and omphalitis between groups. However, parity 3 sows and all-parity analyses showed higher frequency of piglets with arthritis and facial lesions. The UTI (+) group showed lower AWW than the UTI (-) group in parity 4 sows and in all-parity analyses applied to growth performance. In conclusion, UTI in sows during pregnancy is a risk factor for arthritis and facial lesions in suckling piglets, as well as has negative effect on their growth performance.